Short-Term Effects of Conversion to Direct Seeding Mulch-Based Cropping Systems on Macro-Fauna and Weed Dynamics. Issue 1 (2nd January 2016) - Kulagowski, Rémy; Riggi, Laura; Chailleux, Anaïs
ABSTRACT: Agroecosystem biodiversity could provide essential services such as pest control. One approach currently used to promote ecosystem services in agricultural systems is to reduce tillage and increase plant diversity. In this study, we assessed the short-term effects of conversion from reduced tillage (RT) to direct seeding mulch-based cropping systems (DMC) on the dynamics of arthropods (detritivores and predators), and major pests (slugs and weeds). The study was conducted in two commercial fields: one cropped with sorghum ( Sorghum bicolor L.) and one with maize ( Zea mays L.). We found that both beneficial and detrimental groups monitored were more abundant in DMC than in RT treatment and that the dominant species differed between treatments. Because of their major role in agroecosystems by contributing to the control of weed seeds, insects, and slugs, carabid beetles (Carabidae) were investigated in greater detail, and the results showed their diversity was also higher in DMC than in RT. The dominant species found were Poecillus cupreus and Pseudofonus rufipes in the maize and sorghum fields, respectively. The increase in biological control agents shortly after conversion suggested that cover crops should be considered as a pest management tool, even on a short-term scale.